The Influence of Product Innovation and Social Media Marketing on Mochi Cake Purchasing Decisions in Sukabumi City by Mediation of Brand Perception Studies on Brand Mochi XYZ - Rahmaida, Elga; Pranowo, Agus Setyo; Limakrisna, Nandan (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
The level of competition in the business world, especially in the culinary field in Indonesia, is very tight. Currently, market conditions are increasingly dynamic, requiring business people to continuously improvise and innovate in order to retain their customers. Because, every company is always trying to increase market share and reach new customers. This study consisted of 100 respondents who had bought mochi brand XYZ cakes more than twice, and this research used quantitative data sources from questionnaires. The sampling method uses probability sampling with convenience sampling techniques. The research results show 1) Product innovation has a positive and significant impact on brand perception. 2) Social Media Marketing Has a Positive and Significant Influence on Brand Perception 3) Product Innovation has no significant effect on Purchasing Decisions 4) Social Media Marketing Has a Positive Influence on Purchasing Decisions 5) Brand Perception Has a Positive and Significant Influence on Purchasing Decisions 6) Brand Perception Mediates Influence Between Product Innovation With Purchasing Decisions 7) Brand Perception Mediates Influence Between Product Innovation With Purchasing Decisions.